Case Report: Epstein-Barr virus-positive follicular lymphoma with high PD-L1 expression - Zheng, Xue; Wang, Xuhao; Pan, Yu; Sui, Xiaolong; Yu, Guohua (Frontiers in Immunology, 2025)
BackgroundFollicular lymphoma is a common B-cell lymphoma and is classified as an indolent lymphoma, more frequently seen in middle-aged and elderly individuals. In recent years, considerable research has been conducted on follicular lymphoma; however, cases of Epstein-Barr virus (EBV)-positive follicular lymphoma remain rare. Notably, follicular lymphoma with EBV positivity accompanied by high PD-L1 expression has not been reported.Case presentationWe present a case of EBV-positive follicular lymphoma with high PD-L1 expression and analyze its clinicopathological features. The patient was treated with R-CHOP chemotherapy combined with the anti-CD20 antibody (rituximab), achieving favorable therapeutic outcomes. This case provides valuable insights for the pathological diagnosis and treatment of EBV-positive follicular lymphoma, as well as the role of EBV infection in PD-L1 expression. Furthermore, it raises the question of whether high PD-L1 expression suggests that immunotherapy could serve as another potential treatment strategy for EBV-positive follicular lymphoma.